ANALYSIS OF IMPLEMENTATION PLAN FOR ELECTRONIC ROAD PRICING (ERP) IN TRANSPORTATION SECTOR AT JAKARTA WITH SYSTEM DYNAMICS APPROACH - Oktioza Pratama; Arya Surya Wardana; Fakhri Fadlurrahman (Journal of Information Systems and Management (JISMA), 2022)
The focus of this study is to analyze policy design for Electronic Road Pricing (ERP) that has succeed to reduce congestion in other city like London, Stockholm, and Singapure. System Dynamics model is used as basic for implementation the ERP scenario. Output indicator that analyzed are travel time, Fuel consumption, and CO2 emission. This study shows that ERP can reduce travel time, fuel consumption, and CO2 emission. However, that three output indicators will increase again because the excalation of transport demand. The purpose of implementing ERP is to make the flow of vehicles smoother. This system is able to automatically function like a toll gate without having to reduce or stop the speed of vehicles that will enter the ERP area as it happens on toll roads. Based on the data from the simulation, ERP revenue is generated with the following assumptions: The ERP implemented is Complete road pricing so that it is implemented on a scale of one city of Jakarta, all car and motorcycle trips that have moved due to the ERP are assumed to have moved to public transportation that does not use road capacity such as Transjakarta and KRL. ERP revenue tends to increase from year to year with an average annual income of IDR 46,079,710,631,574.00 per year. This revenue tends to increase from year to year considering the increase in total commuting trips each year. This is due to the increase in the population of the city of Jakarta which has increased from year to year.